Euphorbia guyoniana دراسة النشاطية البيولوجية لمستخلصات نبتة - دويس, كوثر; دربال, علاء الدين; بن علي, سارة (Université of eloued جامعة الوادي, 2025)
The effect of aqueous and methanolic (aerial and root) extracts of Euphorbia guyoniana, which was harvested from Al-Bayada area in Oued Souf, was studied. The study aims to determine the ability of these extracts to inhibit free radicals and bacteria growth, in addition to inhibiting one of the important enzymes that have a key role in raising the level of sugar in the blood (α-amylase). The process of extracting the active compounds of E.guyoniana was done by cold soaking using two solvents, water and methanol for its separate parts (aerobic/radical), and the methanolic extract of the root had the greatest efficiency in the extraction. Phytochemical detection of different groups of secondary metabolites showed that this plant contains a group of compounds that can be biologically active, namely phenolic compounds, tannins, flavonoids, terpenes and sterols. By using chromatic methods, the results obtained showed that the aerial and root parts of the plant contain these metabolites, except for the flavonoids that were absent from the root. Stem and leaf anatomy of the plant shows that the stem is characterized by the presence of latex-secreting glands and the absence of stomata on the axial surface of the leaf. Measuring the antioxidant activity of the various extracts was done using the DPPH root displacement method. The results showed that all extracts had an inhibitory response to free radicals. DPPH varied in intensity according to the type of solvent and the plant part. It was noted that the two methanolic extracts had the highest antioxidant activity. The best is 0.019±0.164(mg/ml). In a second step, the antibacterial activity was measured, as the results showed that the aqueous extracts had no effect on the bacterial species used in the study, while there was an effect on all these species in the methanolic extracts, especially the aerobic part. =
التنوع الحيوي و فيسيولوجيا النبات
Keywords: Euphorbia guyoniana; extracts; secondary metabolites; antioxidant activity; alpha-amylase inhibition; antibacterial activity.